Luminescence of phosphorus doped silica glass - Trukhin, Anatoli N.; Antuzevics, Andris; Golant, Konstantin M.; Griscom, David L. (Elsevier B.V., 2017)
A fiber preform with P-doped silica core is studied by luminescence methods. P-doped silica was synthesized via the SPCVD method on a substrate tube made of pure silica glass F300. Two luminescence bands were detected under excitation of the F2 excimer laser (157 nm). One band is in UV range at 4.6 eV (265 nm) with two time constants ~ 30 ns and 5 μs and the other at 3.1 eV (400 nm) with time constant ~ 5.5 ms. Fast decay of the blue band with time constant ~ 20 ns was also observed. The main excitation band of the UV luminescence is at 7.1 eV (~ 170 nm) and that for blue band is at 6.3 eV (~ 195 nm). These bands belong to two different luminescence centers, however, both are associated with the presence of phosphorus. The UV band is similar to the one observed in many different oxide materials containing phosphorus and is ascribed to PO43- complex ion. The blue band is ascribed to a twofold coordinated phosphorus. Both the blue and the UV luminescences participate in the recombination process due to electron trapping. These luminescences appear due to thermal stimulation upon recombination of liberated self-trapped holes. Other than the detected phosphorus-related oxygen-hole-centers, there is no other recombination luminescence.
This work is supported by Material Science program IMIS2 of Latvia.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Silica; phosphorus; germanium; time resolved luminescence; Recombination luminescence